Macroalgae community structure on Kumeke Island, East Bolaang Mongondow Regency, North Sulawesi Province, Indonesia - Valina, Rahmi; Asthisa, Dias; Pangalila, Novelia M.A.; Timumu, Farhan A.; Kasim, Fitra M.A. (AQUATIC SCIENCE & MANAGEMENT, 2024)
Macroalgae is one of the potential biological resources in Indonesian waters that has many important roles, from an ecological to an economic perspective. The aim of this research is to analyse the structure of macroalgae communities found in the waters of Kumeke Island, East Bolaang Mongondow Regency, Indonesia. The method used in this research is a survey with descriptive data analysis. Determining the sampling station point is carried out by purposive sampling, namely by selecting an area based on the presence of macroalgae. Macroalgae sampling used the line transect method with a quadratic sampling technique with a size of 1.5 x 1.5 m. The research results showed that the types of macroalgae found were 11 species, consisting of 3 species of Chlorophyta, 4 species of Phaeophyta, and 4 species of Rhodophyta. The density of macroalgae species is dominated by Rhodophyta (38%), Phaeophyta (31%), and Chlorophyta (30%). The total density of macroalgae is 9–46 ind/m². The diversity index ranges from 1.154 to 2.234 in the medium category, the uniformity index ranges from 0.481 to 0.932 in the high category, and the dominance index ranges from 0.114 to 0.338 in the low category.